Dynamic performance of RC beam-column substructures under the scenario of the loss of a corner column - experimental results - Kai, Qian (2012)
Six one-third scale reinforced concrete (RC) beam-column substructures, each with different design detail, span length and span aspect ratio, were designed and tested to investigate the dynamic load redistribution performance of RC substructures following predefined initial damage. The initial damage was caused by the sudden removal of the corner support. The tested variables include: the longitudinal and transverse reinforcement ratio in the beams, columns and joints, design span length and span aspect ratio. Extensive instrumentation was installed in predetermined locations on the tested specimens prior to conducting the tests, recording data such as acceleration, velocity and displacement distribution. The histories of the bending moments, as well as the vertical and horizontal reaction forces at the fixed supports were also noted. The test results indicated that the column removal apparatus was effective and confirmed that the design span length significantly affected the capability of the frames to resist progressive collapse. Furthermore, it was demonstrated that seismically detailed specimens could mount a more robust performance in resisting progressive collapse.